PERBEDAAN KEMAMPUAN BERPIKIR KRITIS SISWA YANG MENGGUNAKAN MEDIA PEMBELAJARAN LINGKUNGAN DENGAN MEDIA GAMBAR MATA PELAJARAN IPA DI KELAS 5 SD NEGERI 2 PATOKAN KABUPATEN SITUBONDO - Eko Hadi Purwanto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2017)
The devolopment of student’s critical thinking in Situbondo, especially in subdistrick of Panji can be said it still low.This was said by the head of teacher working group (KKG) in state primary school Patokan 2 Situbondo. This is proven when students were joining Olympics Championship, theirposition were in the middle,compare to other the participants from other sub-district. There were many teachers who still dominate the learning process and students were only as an object. Thus,It is needed a change in teaching learning process, that should be implemented by teachers to improve the student’s critical thinking skills in learning science subject,for instance, by using the natural environmental approach. The research was conducted in class 5 SD Negeri 2 Patokan Situbondo many as 42 students consisting of 21 students of class 5A and 5B class of 21 students.This study aims to determine differences in learning model that uses media with media images of the environment on students' critical thinking skills. The sample consists of two classes of experimental class (VA) and the control class (VB) in SD Negeri 2 Patokan Situbondo cluser selected by random sampling technique. Data obtained in the form of quantitative and qualitative data. Quantitative data is data obtained from the average value of post-test were analyzed using Liliefors Test and Test-F (homogeneity of variance) at significance level of 5%. While the qualitative data in the form of student learning activities derived from the observation and analyzed descriptively. The results showed that an increase kemamuan critical thinking of students in the experimental class. The average post-test experimental class is 80,71. Based on the results of t-test values ​​obtained thitung 3,55 > ttabel 2,02108 then the corresponding basis for decision making in the t-test, it can be concluded H0 rejected and Ha accepted. The average percentage of students in all aspects of the activity observed in the experimental class berkriteria fairly good (80%). Nevertheless, the increase in critical thinking skills that occur in the experimental class have differences with improved critical thinking skills that occur in the control class. Increasing students' critical thinking experimental class is higher than the increase in critical thinking control class. Thus, it can be concluded even if there are no significant differences in the ability of critical thinking between the experimental class and control class, but the application of learning strategies to influence the media environment ability students' critical thinking